Peptide IDR-1002 Inhibits NF-κB Nuclear Translocation by Inhibition of IκBα Degradation and Activates p38/ERK1/2–MSK1-Dependent CREB Phosphorylation in Macrophages Stimulated with Lipopolysaccharide - Huante-Mendoza, Alejandro; Silva-García, Octavio; Oviedo-Boyso, Javier; Hancock, Robert E. W.; Baizabal-Aguirre, Víctor M. (Frontiers in Immunology, 2016)
The inflammatory response is a critical molecular defense mechanism of the innate immune system that mediates the elimination of disease-causing bacteria. Repair of the damaged tissue, and the reestablishment of homeostasis, must be accomplished after elimination of the pathogen. The innate defense regulators (IDRs) are short cationic peptides that mimic natural host defense peptides and are effective in eliminating pathogens by enhancing the activity of the immune system while controlling the inflammatory response. Although the role of different IDRs as modulators of inflammation has been reported, there have been only limited studies of the signaling molecules regulated by this type of peptide. The present study investigated the effect of IDR-1002 on NF-kB and CREB transcription factors that are responsible for triggering and controlling inflammation, respectively, in macrophages. We found that TNF-alpha and COX-2 expression, IkBalpha phosphorylation, and NF-kB nuclear translocation were strongly inhibited in macrophages pre-incubated with IDR-1002 and then stimulated with lipopolysaccharide (LPS). IDR-1002 also increased CREB phosphorylation at Ser133 via activation of the p38/ERK1/2-MSK1/2 signaling pathways without detectable expression of the cytokines IL-4, IL-10 and IL-13 involved is suppressing inflammation or alternative activation. Transcriptional activation of NF-kB and CREB is known to require interaction with the transcriptional co-activator CREB-binding protein (CBP). To test for CBP-NF-kB and CBP-CREB complex formation, we performed co-immunoprecipitation assays. These assays showed that IDR-1002 inhibited the interaction between CBP and NF-kB in macrophages stimulated with LPS, which might explain the inhibition of TNF-alpha and COX-2 expression. Furthermore, the complex between CBP and CREB in macrophages stimulated with IDR-1002 was also inhibited, which might explain why IDR-1002 did not lead to expression of IL-4, IL-10 and IL-13, even though it induced an increase in phospho-CREB relative abundance. In conclusion, our results indicated that IDR-1002 has a dual effect. On one hand, it inhibited NF-kB nuclear translocation through a mechanism that involved inhibition of IkBalpha phosphorylation, and on the other it activated a protein kinase signaling cascade that phosphorylated CREB to selectively influence cytokine gene expression. Based on or results we think IDR-1002 could be a potential good biopharmaceutical candidate to control inflammation.